Shallow Gas Prospect Evaluation in Shahbazpur Structure Using Seismic Attributes Analysis - a Case Study for Bhola Island, Southern Bangladesh - Rahman, Morshedur; Kabir, SM Mainul; Lupin, Janifar Hakim (Dhaka University Journal of Science, 2016)
Shahbazpur structure is located in the southern Part of the central deep basin in the Hatia trough, where lie all the largest Gas fields of Bangladesh. A method is established to delineate the structural mapping precisely by interpreting four 2D seismic lines that are acquired over Shahbazpur structure. Moreover direct hydrocarbon indicators (DHI) related attributes are analyzed for further confirmation for presence of hydrocarbon. To do this synthetic seismogram generation, seismic to well tie, velocity modelling and depth conversion are performed. A limited number of seismic attributes functions that are available in an academic version of Petrel software are applied to analyze attributes. Seismic attribute analyses that are used in this interpretation mainly are associated to bright spot detection. Presence of bright spots or high amplitude anomaly over the present Shahbazpur structure, reservoir zone are observed. This signature will play a very important role in next well planning on the same structure to test the shallow accumulation of hydrocarbon. For better understanding of this shallow reserve, it is suggested to acquire 3D seismic data over Shahbazpur structure which will help to evaluate the hydrocarbon accumulation and to identify gas migration pathways. Dhaka Univ. J. Sci. 64(2): 135-140, 2016 (July)